New Terrorism: What Can the History of Terrorism Contribute? - Nazala, Rochdi Mohan (Jurnal Hubungan Internasional, 2019)
Whether or not the realm of terrorism has significantly transformed in the past three decades is one of major debates in the field of political violence today. Proponents of new terrorism argue that current terrorists are more religious inspired and lethal, depend less on state’s support and have changed their nature in term of organizational structure. On the other hand, some refuse the idea of new terrorism and, instead, argue that there is only continuity regarding terrorist acts. This paper attempts to clarify the debates through a historical investigation within the history of terrorism and it reveals that characteristics brought by the concept of new terrorism are valid to describe the current status of terrorism. However, by looking at some evidences in terrorism history, this paper also found out that those features are less unique to terrorism operatives nowadays due to the fact that perpetrators’ activities in the past have similar attributes.